Design of Attendance System for Pemalang Diskominfo Employees Using Design Thinking Method (Universitas Negeri Semarang, 2021)
Employees are an important part of carrying out the obligations of the Communication and Information Office (Kominfo) Pemalang Regency. However, the management of employee data for recording attendance at the Department of Communication and Information of Pemalang Regency is still processed manually, so that the attendance process management is considered ineffective and inefficient. Therefore, it is necessary to create an Employee Presence System that can manage employee attendance data. The goal is to facilitate the process of managing employee attendance data and making attendance data more precise. A data collection method is applied in making the system is an interview. In the interview, consultations and direct questions and answers were conducted with the field supervisor regarding the system requirements to be made. The design of this system uses the design thinking method. The design thinking method is carried out sequentially from one stage to another. There are five stages in the design thinking method: empathy, determination, ideas, prototypes, and testing. From making a system with this method, a design for an employee attendance system is produced that is comfortable to look at and easy to use in all circles.